Preparing tutors for online collaborative learning at the Open University Malaysia - Zoraini Wati Abas,; Kaur, Abtar (2007)
To be more effective, open and distance learning programmes should incorporate collaborative learning environments with the purpose of engaging learners in the learning process. This will eventually develop into a learning community that would help, among others, to reduce the feeling of loneliness and isolation commonly felt among distance learners. A study to determine the perceptions of tutors on online collaborative learning, particularly in how tutors viewed online collaborative learning at the Open University Malaysia (OUM) was conducted. Their online pattern of collaboration was also determined. The paper highlights the research and its findings and provides suggestions on future training of the tutors to help ensure the success of online collaborative learning at the university. The findings will be useful to those who are designing tutor training programmes for online collaborative learning.